Highly sensitive assay for the determination of therapeutic peptide desmopressin in human plasma by UPLC-MS/MS - Shiva Kumar Gudlawar; Nageswara Rao Pilli; Sridhar Siddiraju; Jaya Dwivedi (Elsevier, 2017)
An analytical method based on ultra-performance liquid chromatography with positive ion electrospray ionization (ESI) coupled with tandem mass spectrometry detection (UPLC-MS/MS) was developed and validated for the determination of therapeutic peptide desmopressin in human plasma. A desmopressin stable labeled isotope (desmopressin d8) was used as an internal standard. Analyte and the internal standard were extracted from 200 µL of human plasma via solid-phase extraction technique using Oasis WCX cartridges. The chromatographic separation was achieved on an Aquity UPLC HSS T3 column by using a gradient mixture of methanol and 1 mM ammonium formate buffer as the mobile phase. The calibration curve obtained was linear (r2≥0.99) over the concentration range of 1.01-200 pg/mL. Method validation was performed as per FDA guidelines and the results met the acceptance criteria. The results of the intra- and inter-day precision and accuracy studies were well within the acceptable limits. The proposed method was successfully applied to pharmacokinetic studies in humans.